Phonosemantic component of bilingual mental lexicon: word recognition models and lexical selection mechanisms - S.O. Gaivoronskaya (Язык и текст)
Context and relevance. The study of the significance of the graphic form of words in the perception and interpretation of their phonosemantic component determines a new approach to assessing the influence of the learnt language on the primary linguistic personality and makes it possible to define a new vector of development of the theory of teaching foreign language. Objective. The article is aimed at determining the role of the cognate effect in assessing the linguistic awareness and flexibility of the mental lexicon of speakers of two languages. Hypothesis. The method of psycholinguistic experiment on lexical decision making has been used earlier in studies of speech pathologies and other pathological conditions, but it is the main means of studying national language consciousness to reveal patterns in word identification. Methods and materials. The method of phonosemantic analysis is oriented to the study of the structure of a particular language and the prima facie motivation of its linguistic sign. Also within the framework of work on this article the somatic method of objective analysis, in particular registration of eye movements, is applied.